Thematic Analysis of President Akufo-Addo’s 2023 State of the Nation Address - Emmanuel Botchwey; Stephen Kwaku Duah; Douglas Adade (Linguistics Initiative, 2023)
This study examines the items given prominence in President Akufo-Addo’s 2023 State of the Nation Address. As a qualitative research with textual analysis design, the study adopted the Theme-Rheme model of Halliday and Matthiessen’s (2014) Systemic Functional Linguistics theory with which the clause is construed as a message. The findings of the study indicate that (1) topical, interpersonal and textual Themes have their representation and distribution in the text. The most frequent ideational/topical Theme used in English is Participant followed by Circumstance. Process is the least thematised experiential. The textual Theme include mostly conjunctions, followed by conjunctive adjuncts. Interpersonal Theme includes mostly vocatives and few modal adjuncts and very few finite verbal operators. The elements of the topical Theme which present the core content of the message include; Participant such as Actor, Scope, Senser, and Identified – realized by pronouns and nominal group; Circumstantial of Temporal Location, Duration, Manner, Cause, Accompaniment, Role, Angle of Viewpoint. The study could be a significant contribution to scholarship in functional grammar, particularly in Theme-Rheme analysis of English use in ESL context. It demonstrates how a grammatical theory highlights foregrounding of experiences in a discourse and facilitating text composition and comprehension.